Increased Commitment to the Organization through Strengthening Organizational Culture, Learning Organization and Personality (Empirical Study Using Correlational Approach and SITOREM Analysis on State Senior High School Teachers in East Jakarta) - Sobirin, Sobirin; Abdullah, Thamrin; Sunaryo, Widodo (Budapest International Research and Critics University, 2021)
The goal of this research is to uncover ways to improve organizational commitment in East Jakarta State Senior High Schools by examining organizational culture, learning organization, and personality. These attempts are made possible by identifying the strengths that exist between these variables. This study incorporates a correlational technique as well as SITOREM Analysis. To see if organizational culture, learning organization, and personality factors have a good association with organizational commitment, correlational statistical approaches are applied. The SITOREM analysis is used to identify the priority order as well as recommendations for improving the required indicators. All variables were positively connected to organizational commitment, according to the findings of a research of 39 East Jakarta State Senior High Schools. Personality r y3 = 0.684 (p0.01), organization culture r y1 = 0.644 (p0.01), and learning organization r y2 = 0.684 (p0,01) are the findings of the correlation strength sequence based on the highest correlation. The SITOREM Analysis Results suggest that agreeableness, inventiveness, aggressiveness, system thinking, and mental models are the markers that need to be improved. The proposal that might be made is that the school should provide ongoing advice to instructors, particularly in terms of organizational compliance, in order for teachers to enhance their commitment to the organization.